Evaluation of proposed staging systems for human papillomavirus‐related oropharyngeal squamous cell carcinoma. Issue 10 (5th January 2017) - Malm, Ian‐James; Fan, Caleb J.; Yin, Linda X.; Li, David X.; Koch, Wayne M.; Gourin, Christine G.; Pitman, Karen T.; Richmon, Jeremy D.; Westra, William H.; Kang, Hyunseok; Quon, Harry; Eisele, David W.; et al.
Abstract : BACKGROUND: Patients with human papillomavirus (HPV)‐related oropharyngeal cancer (OPC) have improved survival when compared with those with HPV‐negative OPC. Unfortunately, the American Joint Committee on Cancer seventh edition (AJCC‐7ed) staging system does not account for the prognostic advantage observed with HPV‐positive OPC. The purpose of the current study was to validate and compare 2 recently proposed staging systems for HPV‐positive OPC. METHODS: Patients treated for HPV‐positive OPC from 2005 to 2015 at Johns Hopkins Hospital (JHH) were included for analysis. The International Collaboration on Oropharyngeal cancer Network for Staging (ICON‐S) and The University of Texas MD Anderson Cancer Center (MDACC) staging systems were applied and survival was calculated using Kaplan‐Meier methods. Cox proportional hazard regression was used to determine the relationship between stage of disease and survival. Models were compared using the Akaike information criterion (AIC). RESULTS: A total of 435 patients were eligible for analysis. There was a dramatic shift in lymph node category and overall stage of disease when ICON‐S and MDACC stage were applied to the JHH cohort. There was superior stratification of overall survival and progression‐free survival by ICON‐S stage. Both proposed models had an improved fit based on AIC scores ( P <.001 for both) over the AJCC‐7ed. The ICON‐S staging system had the lowest AIC score, and thus a better fit within the JHH population. CONCLUSIONS: The current analysis provides external validation for both staging systems in an independent and heterogeneously treated patient population. Although the MDACC staging system is an improvement over the AJCC‐7ed, the ICON‐S stage provides superior stratification of overall and progression‐free survival, thereby supporting its use as the updated AJCC staging system for OPC. Cancer 2017;123:1768–1777 . © 2017 American Cancer Society . Abstract : In a cohort of patients who were treated heterogeneously (including primary surgery), the International Collaboration on Oropharyngeal cancer Network for Staging (ICON‐S) staging system appears to provide superior stratification of overall and progression‐free survival. While providing external validation for both staging systems, the current analysis supports the use of the ICON‐S staging system in the anticipated update to the American Joint Committee on Cancer staging system for oropharyngeal cancer.